North South Connectivity: Opportunities and Challenges in National Security and Development - Koirala, Sabin (Unity Journal, 2022)
After the long decade civil conflict, Nepal has been moving through a transitional phase for the development and prosperity. Comparing among the landlocked state, the indicators depict low level of infrastructure development. Being landlocked and mountainous country, Nepal has high trading cost due to difficult geography and lack of reliable infrastructures, decreasing the competitiveness domestically and internationally. North South connectivity not only connects China and India but also revives the role of Nepal as land linked. Nepal is always trying to boost economic growth using liberalization, decentralization policy and now transforming the unitary state to federal state. The growing expectation of people towards prosperity and development has driven the state to make investment on large scale connectivity projects in transport, energy, aviation, communication sector. Having resource constraints, state should mobilize the scarce resources in rational and optimum ways to maximize the development opportunities and mitigate the security challenges and threats. Furthermore, it is necessary to assess both long term and short-term impact during strategic project formulation. This paper aims to identify opportunities and challenges of cross boarder connectivity in national security and development using various information and fact through secondary sources and with the examples of other nations sharing similar attributes. Findings suggested that Nepal should develop multimodal connectivity strategies while considering strategic location of Nepal and shall utilize international assistance and support while maintaining the relationship with neighbors, regional power and great power based on sovereign equality, mutual respect, and benefits. Further, this study contributes to policy makers and planners for the appraisal of strategically important projects.